Rational drug prescribing and dispensing in tertiary care teaching hospital of Western Nepal - Upadhyay, DK; Palaian, S; Shankar, PR; Mishra, P (Journal of Institute of Medicine Nepal, 2009)
Background: Previous studies have acknowledged that irrational use of medicines is a problem in Nepal. Studies from the Manipal Teaching Hospital have identified lacunae in prescribing and recommended interventions to improve the drug use pattern in the hospital. Educational and managerial interventions have been carried out to improve the use of medicines. Objectives: The study was conducted with the objectives of analyzing the prescriptions for rational prescribing and dispensing, and to evaluate the patient's knowledge regarding use of drugs as per the International Network for Rational Use of Drugs (INRUD)/WHO indicators. Methods: The prescription and labeling of the dispensed drugs were checked for their accuracy and necessary details were entered in the encounter form developed as per the INRUD/WHO indicators. Patients were interviewed for their knowledge regarding dose, duration, and frequency of the drug prescribed. The filled encounter forms were analyzed for the results. Results: The average drugs per prescription were 2.53. Only 16.38% of drugs were prescribed by generic name and 18.08% of the total drugs were fixed-dose combinations. It was found that only 37.09% and 31.06% of the drugs prescribed were from the Essential drug list of Nepal and WHO Essential drug list respectively. A very high percentage (97.92%) of the drugs was prescribed from the hospital drug list and 47.75% of the drugs were from the Nepalese National Formulary. The average cost per prescription was found to be NRs. 224.83 (USD 3.10). It was found that all of the medication envelopes were labeled with name of the drug and time of administration. All the patients knew the duration of the therapy and time of administration time of drugs. Conclusion: The study reported an improvement in the drug use at Manipal Teaching Hospital. There was also a reduction in the prescription cost and improvement in patient knowledge regarding the medications. However, larger studies covering more patients are needed. Keywords: Dispensing, Intervention, Rational prescribing. Journal of Institute of Medicine, August, 2008; 30:2 33-38 The full text of this paper is available from the Journal of Institute of Medicine website